(untitled) (The International Journal for Scientific Research, 2023)
Introduction: Needlestick and sharp object injuries represent a significant occupational hazard faced by healthcare workers worldwide. A systematic review focusing on needlestick and sharp object injuries among healthcare workers is essential due to the heterogeneous nature of existing research. The aim of this systematic review is to comprehensively synthesize existing literature to provide a comprehensive understanding of the prevalence, risk factors, and prevention strategies related to needlestick and sharp object injuries among healthcare workers. Methods: This thorough examination adheres to PRISMA principles and implements a pre-planned research plan to promote transparency and minimize partiality. It encompasses investigations involving medical personnel (such as nurses and physicians) centered on puncture wounds and sharp instrument mishaps, exploring contributing factors, occurrence rate, aftermaths, and preventative measures. A thorough exploration is conducted through various databases, with two separate evaluators examining and evaluating the studies. Suitable studies encompass both observational and intervention-based studies without constraints on publication dates. Information is extracted using a standardized format, and ethical clearance is not required as the review solely relies on already published data. Results: In our systematic review, we initially identified 1,523 articles through a database search, which underwent a stepwise screening process, resulting in 198 articles after assessing titles and abstracts. Subsequently, these 198 articles underwent a rigorous full-text evaluation. After this thorough assessment, 14 studies were included that met our predefined eligibility criteria. Our synthesis of the observational studies revealed recurring risk factors for needlestick and sharp object injuries among healthcare workers, including inadequate training, the impact of fatigue and extended working hours, and insufficient personal protective equipment (PPE). Additional factors like job category, experience level, and compliance with safety protocols were also highlighted in specific studies. Conclusions: This systematic review highlights the importance of standardized approaches to enhance healthcare worker safety, particularly in addressing risk factors like inadequate training, fatigue, and inadequate personal protective equipment (PPE). The effectiveness of prevention strategies, as demonstrated in our meta-analysis, underscores the value of comprehensive programs in reducing injury rates, emphasizing the need for more standardized and multifaceted safety measures across healthcare settings.